2022
DOI: 10.1002/joc.7681
|View full text |Cite
|
Sign up to set email alerts
|

The Orinoco low‐level jet during El Niño–Southern Oscillation

Abstract: This study shows the influence of El Niño-Southern Oscillation (ENSO) over the seasonal and diurnal variability of the Orinoco low-level jet (OLLJ) during the December-January-February (DJF) season. Results show changes in the occurrence and intensity of the OLLJ winds during the phases of ENSO (El Niño and La Niña) in relation to Neutral conditions. During El Niño (La Niña), the OLLJ days decrease (increase) over the mid and exit of the OLLJ corridor. Furthermore, the mean wind vertical profiles (and the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…The ChocoJet winds show PS with precipitation over western Colombia for both states of ENSO, which can be associated with the increase (decrease) in ChocoJet winds during LN (EN) and the increase (decrease) in precipitation over western Colombia (Poveda & Mesa, 2000). Finally, some PS spatial patterns for precipitation and low‐level winds at 925 hPa are coincident over the LLJ regions, these results suggest phase synchrony between low‐level winds and precipitation, relationship that have been mentioned using other approaches for each LLJ case by Wang (2007); Poveda and Mesa (2000); Builes‐Jaramillo et al (2022a, 2022b).…”
Section: Final Remarks and Future Worksupporting
confidence: 69%
See 1 more Smart Citation
“…The ChocoJet winds show PS with precipitation over western Colombia for both states of ENSO, which can be associated with the increase (decrease) in ChocoJet winds during LN (EN) and the increase (decrease) in precipitation over western Colombia (Poveda & Mesa, 2000). Finally, some PS spatial patterns for precipitation and low‐level winds at 925 hPa are coincident over the LLJ regions, these results suggest phase synchrony between low‐level winds and precipitation, relationship that have been mentioned using other approaches for each LLJ case by Wang (2007); Poveda and Mesa (2000); Builes‐Jaramillo et al (2022a, 2022b).…”
Section: Final Remarks and Future Worksupporting
confidence: 69%
“…For example, (i) the Caribbean LLJ (CLLJ) has a different relationship with ENSO during its active seasons (JJA and DJF). During DJF, a weak (strong) easterly CLLJ corresponds to warm (cold) SST anomalies in the tropical eastern and central Pacific, whereas in JJA, a strong (weak) easterly CLLJ is associated with warm (cold) SST anomalies in the tropical Pacific (Wang, 2007); (ii) The ChocoJet, which is active during SON, is associated with an reduction (increase) in precipitation over western Colombia during EN (LN) (Poveda & Mesa, 2000; Yepes et al, 2019) and (iii) The Orinoco LLJ (OLLJ), which is active during DJF and during EN (LN), the mean wind vertical profiles (and the intensity of the diurnal cycle) decreased (increased) up to 24% (15%) (Builes‐Jaramillo et al, 2022a, 2022b). Although there have been advances in our understanding of the relationships between ENSO and precipitation in the NSA and FEP, questions remain and we are still far from a robust understanding of the impacts, inter‐basin climate interactions and possible consequences in the context of climate change (Cai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…(2014) showed that the Tropical North Atlantic and the far eastern tropical Pacific are connected through aerial rivers that flow over the Amazon River basin and the Andes, particularly from April to October. Also, the Tropical North Atlantic feeds the easterly trade winds and the Orinoco LLJ which in turn hits the foothills of the Eastern Andes providing the input moisture and energy for diverse land‐atmosphere interactions as initiating convective processes (Builes‐Jaramillo et al., 2022; Espinoza et al., 2020; Jimenez‐Sánchez et al., 2019; Poveda et al., 2020). As reported in previous studies, northwestern Amazon modulates moisture sources for continental precipitation (Dominguez et al., 2022; Gimeno et al., 2012; Poveda et al., 2014; Staal et al., 2018; Weng et al., 2018; Zemp et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The CA block westerly and easterly winds that are primary sources for the high rainfall rates witnessed in the Pacific and Orinoco boundaries. These regions are sensitive to ENSO‐related variability (Figures 7 and 8) and are part of the complex mechanism of interaction between low‐level jets such as the Chocó (Poveda et al., 2014, 2020), Caribbean (Amador, 2008; Durán‐Quesada et al., 2012; Poveda & Mesa, 1999), and Orinoco (Builes‐Jaramillo et al., 2022; Jiménez‐Sanchez et al., 2019; Martínez et al., 2022). Finally, the assumption of well‐mixing of advective and evaporative sources of atmospheric vapor needs to be better evaluated in the context of the Colombian Andes for WAM‐2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation